2016
DOI: 10.1177/0300060516638992
|View full text |Cite
|
Sign up to set email alerts
|

The effect of anticancer therapy on anti-hepatitis B antibody titres in patients with haematological malignancies and solid tumours

Abstract: ObjectiveTo investigate the effect of immunosuppressive anticancer therapy on titre levels of anti-hepatitis B surface antibodies (anti-HBs) in hepatitis B surface antigen (HBsAg) negative and anti-HBs positive patients with haematological malignancies or solid tumours.MethodsThis retrospective study reviewed the medical records of patients with haematological malignancies or solid tumours. Pretreatment HBsAg negative and anti-HBs positive patients were included in the analysis. Anti-hepatitis B core antibody … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…8 The clinicians started to be aware of the importance of preemptive HBV testing after increasing number of reactivations in risk groups reported in the literature due to improper screening strategies. 10,11 The lack of knowledge, experience and local references could be the reasons for previous improper screenings. We did not have our own guideline in our institution.…”
mentioning
confidence: 99%
“…8 The clinicians started to be aware of the importance of preemptive HBV testing after increasing number of reactivations in risk groups reported in the literature due to improper screening strategies. 10,11 The lack of knowledge, experience and local references could be the reasons for previous improper screenings. We did not have our own guideline in our institution.…”
mentioning
confidence: 99%
“…Fewer studies (16) evaluated HBVr secondary to chemotherapeutic agents without rituximab for hematological malignancy or solid tumor (Table 3). 48,49,53-66 Only 2 studies reported the receipt of prophylaxis. Among the 2041 patients evaluated, 54 (2.6%) experienced HBVr.…”
Section: Resultsmentioning
confidence: 99%
“…The present study showed that the patients' anti-HBs titers were decreased after therapy compared with before therapy (a median of 29.75 vs. 6.45 IU/L, respectively). Yılmaz et al 14 found that the posttreatment anti-HBs seronegativity rate was higher in the patients who had pretreatment antibody titers lower than 100 IU/L. (p < 0,001).…”
Section: Discussionmentioning
confidence: 97%